2012
DOI: 10.1242/jcs.102152
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Rbpj signaling is required for the development of noradrenergic neurons in mouse locus coeruleus

Abstract: SummaryThe locus coeruleus (LC) is the main source of noradrenaline in the brain and is implicated in a broad spectrum of physiological and behavioral processes. However, genetic pathways controlling the development of noradrenergic neurons in the mammalian brain are largely unknown. We report here that Rbpj, a key nuclear effector in the Notch signaling pathway, plays an essential role in LC neuron development in the mouse. Conditional inactivation of Rbpj in the dorsal rhombomere (r) 1, where LC neurons are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 82 publications
(100 reference statements)
2
14
0
Order By: Relevance
“…57-60 The Notch intracellular domain is then transported to the nucleus where it binds to transcription factors on gene promoters, inducing changes in gene expression. 73, 74 A recent study reported that RBPJ-κ may play a role in the expression of DDC and MAOA , 61 and we showed that RBPJ-κ KD resulted in increased expression of TPH1/2 , DDC , and SLC6A4 in SK-N-BE(2) neuroblastoma cells ( Supplementary Figure 7 ). Obviously, future studies will be required to clarify the possible functional relationships among ADAM10, TSPAN5, Notch and RBPJ-κ.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…57-60 The Notch intracellular domain is then transported to the nucleus where it binds to transcription factors on gene promoters, inducing changes in gene expression. 73, 74 A recent study reported that RBPJ-κ may play a role in the expression of DDC and MAOA , 61 and we showed that RBPJ-κ KD resulted in increased expression of TPH1/2 , DDC , and SLC6A4 in SK-N-BE(2) neuroblastoma cells ( Supplementary Figure 7 ). Obviously, future studies will be required to clarify the possible functional relationships among ADAM10, TSPAN5, Notch and RBPJ-κ.…”
Section: Discussionsupporting
confidence: 54%
“…61 Therefore, we knocked down RBPJ-κ in SK-N-BE(2) cells, and observed increased expression of TPH1, TPH2 , DDC , and SLC6A4 ( Supplementary Figure 7 ). This may be one mechanism by which TSPAN5, an integral membrane protein, may influence serotonin biosynthesis, as described in more detail in the Discussion .…”
Section: Resultsmentioning
confidence: 99%
“…Expression was first detected in the brain at E8.0 in the nmesV before neuronal differentiation [34, 56]. We wanted to determine if the relationship between Ascl1 and Notch signalling was similar to that already described in other central nervous system regions [47]. RBPj mutant mice have been commonly used to study the role of Notch inhibition [11, 36].…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, known limitations to the study of Rbpjk/DNA interactions by EMSA are documented. Namely, displaced CSL probes are not always visible in the presence of unlabeled competitors, and formation of an active transcriptional complex in the context of Dll1 exposure may lead to a shift of the nuclear protein bound to the CSL probe and attenuation of the signal [57, 60, 61]. Although the identity of the factors that prevent the association of Rbpjκ with DNA is not known, activation of MAPK in response to PTH may be involved in this process.…”
Section: Discussionmentioning
confidence: 99%